2015
DOI: 10.1017/s1478951515000589
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of health-related quality of life in end-stage chronic obstructive pulmonary disease and non-small-cell lung cancer patients in Serbia

Abstract: A worse QoL, a significantly higher level of depressive symptoms, and adverse socioeconomic status in the COPD group imposes the need for development of more intensive psychosocial and community support for COPD patients during implementation of palliative care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 37 publications
2
23
1
Order By: Relevance
“…Gore et al's lung cancer sample differed from Bausewein et al's in terms of being mostly (72%) men and having received palliative care radiotherapy over the last 12 months in 80% of cases. It was less clear what might have led other studies to differ from the majority by finding depression to be worse in COPD 34,35 or anxiety to be worse in lung cancer, 13 and betweengroup differences in these studies were either mixed 13,34 or less than the 0.5 SD taken to suggest a clinically important difference. 35 As noted above, most studies measuring pain found this to be worse in lung cancer than COPD.…”
Section: Synthesis Of Resultsmentioning
confidence: 87%
“…Gore et al's lung cancer sample differed from Bausewein et al's in terms of being mostly (72%) men and having received palliative care radiotherapy over the last 12 months in 80% of cases. It was less clear what might have led other studies to differ from the majority by finding depression to be worse in COPD 34,35 or anxiety to be worse in lung cancer, 13 and betweengroup differences in these studies were either mixed 13,34 or less than the 0.5 SD taken to suggest a clinically important difference. 35 As noted above, most studies measuring pain found this to be worse in lung cancer than COPD.…”
Section: Synthesis Of Resultsmentioning
confidence: 87%
“…Habraken et al 2 reported similar health-related quality of life between those with COPD or lung cancer, with the COPD group reporting significantly lower scores in physical functioning and general health perceptions. Maric et al 25 found COPD patients scored significantly lower in all SF-36 domains except for pain. Hasegawa et al 23 reported similar scores in the McGill Quality of Life questionnaire but those with COPD had a better psychological state and lung cancer patients had a better support state.…”
Section: Resultsmentioning
confidence: 96%
“…Eleven studies 2,3,5,1825 compared a population with lung cancer to a population with COPD and consisted of retrospective studies of deceased populations ( n = 5), cross-sectional studies ( n = 3), prospective cohort studies ( n = 2) and post-bereavement interviews with caregivers ( n = 1). Three retrospective studies compared a population with COPD to a population with lung cancer of which a proportion (17%–42%) also had co-existing COPD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the prevalence of chronic diseases in cancer patients is substantial (62), we excluded patients chronic diseases' comorbidity since several studies showed that chronic diseases, such as stroke, COPD or chronic kidney disease, significantly further decreases HRQoL in cancer patients (50,(63)(64)(65), A study from Serbia showed that cancer patient with complications showed a higher level of depressive symptoms (65). There was also a substantial reduction on physical and social functioning of breast cancer patients with chronic disease complications (50).…”
Section: Discussionmentioning
confidence: 99%